Influence of different housing systems on prevalence of keel bone lesions in laying hens. Issue 5 (3rd September 2019) - Saraiva, Sónia; Esteves, Alexandra; Stilwell, George
ABSTRACT: The present study aimed to investigate the effect of three housing systems (furnished cages – FC, barns – B, and free-range – FR) on the prevalence and severity of keel bone protrusion and deformations. These health and welfare indicators were measured at the slaughterhouse, using a 4-point scale (0 = absence, 1 = slight, 2 = moderate and 3 = severe). Keel bone deformation was also categorized in relation to the presence of compression over the ventral surface, deviation from a 2D straight plane and deviation from the transverse (C-shaped) or median sagittal (S-shaped) plane. The housing system had a significant effect on prevalence of keel bone deformation ( χ 2  = 45.465, df = 6, P  < 0.001). In FR systems 60.4% of hens presented keel bone deformation, followed by 54.2% in FC and 53.5% in B; however, higher scores for keel bone deformations were more frequent in B systems. Although keel bone protrusion was observed in all laying hen systems, the majority of hens only presented a slight degree (score 1) of protrusion. A positive correlation was obtained for keel bone protrusion and emaciation. The results could be used to initiate detailed investigations into problematic issues that occur during the laying period to improve the health and welfare conditions on farms.